The primate nervous system. - Bloom, Floyd E.; Bjorklund, Anders, 1945-; Hokfelt, Tomas (Handbook of chemical neuroanatomy, 1998)
This volume is the second in the planned coverage of the neurochemical circuitry of the primate central nervous system. While this volume contains only two chapters, their topics and the extraordinarily comprehensive coverage with which the authors have dealt with their topics, will nevertheless contribute equal amounts of knowledge, wisdom, and opportunities for future research extensions as have every volume in this unique series. As such, these chapters extend the goals of this primate series to develop a broad coverage of human and non-human primate chemical neuroanatomic details in a volume which makes clear the known and desirable appreciation for differences between and among subsets of primate brains. The first chapter covers the primate thalamus with equal emphases on new world, old world, pro-simian and human anatomic details and their differences. The second undertakes a comparably comprehensive examination of one of the most intensively studied regions of the primate brain, namely the primate visual cortex. While much has been studied, both chapters also reveal how much remains for future efforts in these enormously important regions which are the archetypes of primate sub-cortical and cortical function.